2015
DOI: 10.1017/s1751731115001111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and dietary lysine on performances and serum and meat traits in finisher pigs

Abstract: A total of 160 Duroc × (Landrace × Large White) pigs, 50% barrows and 50% gilts, of 28.3 ± 4.52 kg of BW were used to study the effect of lysine (Lys) restriction in the finisher period, on growth performances and serum and carcass and meat quality traits. The grower diet (from 30 to 90 kg BW) was slightly Lys-restricted (7.8 g standardised ileal digestible (SID) Lys/kg) in accordance with results from a previous trial. During the finisher period (90 to 130 kg BW), four experimental diets with decreasing SID L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
10
17
2
Order By: Relevance
“…Under ad libitum conditions, barrows are commonly found to consume more feed than gilts (Latorre et al, 2008;Suárez-Belloch et al, 2015a and2015b) which is confirmed by the results of this experiment, being the difference 160 g/day on average. This value is not far from the 220 g/day reported by Rodríguez-Sánchez et al (2011) and explains the faster daily gains recorded in barrows compared with gilts.…”
Section: Growth Performancessupporting
confidence: 84%
See 2 more Smart Citations
“…Under ad libitum conditions, barrows are commonly found to consume more feed than gilts (Latorre et al, 2008;Suárez-Belloch et al, 2015a and2015b) which is confirmed by the results of this experiment, being the difference 160 g/day on average. This value is not far from the 220 g/day reported by Rodríguez-Sánchez et al (2011) and explains the faster daily gains recorded in barrows compared with gilts.…”
Section: Growth Performancessupporting
confidence: 84%
“…Taking into account that the aim of the trial was increasing fatness, a slight impairment of FCR could have been carried out. In fact, in the literature, worse feed efficiency has been reported as a result of dietary protein or Lys restriction in both the grower (D'Souza et al, 2003) and the finisher phase (Campbell et al, 1984;Suárez-Belloch et al, 2015b). The result of the current work is positive, under a productive point of view, but it would indicate that the nutrient restriction generated advancing the finisher diet by 21 days was very limited.…”
Section: Growth Performancesmentioning
confidence: 59%
See 1 more Smart Citation
“…It is commonly accepted that a reduction in dietary net energy (NE) content leads to an increase in feed intake to keep the NE intake constant (Cámara et al, 2016), although the influence of nutrient deficiencies, particularly of indispensable AA, is controversial. Some authors found that voluntary feed intake decreased when pigs were placed on diets that were deficient in protein or indispensable AA (Gallo et al, 2015;Schiavon et al, 2015;Suárez-Belloch et al, 2015), especially tryptophan (Henry et al, 1992;). Other studies found that mild deficiencies in protein, lysine or threonine resulted in increased feed intake (Ferguson and Gous, 1997;Henry, 1995;Chiba et al, 2002).…”
Section: Influence Of Dietary Amino Acid Reduction On Feed Intake Andmentioning
confidence: 99%
“…High IMF content relative to subcutaneous fat is a target of genetic selection. Studies show that intramuscular fat content is highly heritable [19] and is positively correlated (r = 0.45) with subcutaneous fat thickness [20]. However, the physiological function and lipid metabolism ability of different adipose tissues differ [21][22][23].…”
Section: Discussionmentioning
confidence: 99%